Effects of Interrupting Sitting with Use of a Treadmill Desk Versus Prolonged Sitting on Postural Stability - Charalambous, Laura H.; Champion, Rachael B.; Smith, Lindsey R.; Mitchell, Andrew C. S.; Bailey, Daniel P. (International Journal of Sports Medicine, 2019)
High amounts of sitting increase the risk of non-communicable disease and mortality. Treadmill desks make it possible to reduce sitting during the desk-based workerʼs day. This study investigated the acute effect on postural stability of interrupting prolonged sitting with an accumulated 2-h of light-intensity treadmill desk walking. Twenty-one sedentary adults participated in this randomized acute crossover trial, with two 6.5 h conditions: 1) uninterrupted sitting and 2) interrupted sitting with accumulated 2 h light-intensity treadmill desk walking. Pre- and post-condition, participants performed four postural stability tests on a pressure plate (bipedal and unipedal standing stance, eyes open and eyes closed). Anteroposterior center of pressure amplitude showed a significant condition x time interaction in bipedal eyes closed (F(1,20)=4.62, p=0.046) and unipedal eyes open (F(1,20)=9.42, p=0.006) tests, and mediolateral center of pressure amplitude in bipedal eyes closed (F(1,20)=6.12, p=0.023) and bipedal eyes open (F(1,12)=5.55, p=0.029) tests. In the significant interactions, amplitude increased pre to post condition in the uninterrupted sitting condition. The accumulated 2 h light-intensity treadmill desk walking ameliorated the negative effect of 6.5 h prolonged sitting on postural sway, supporting workplace treadmill desk use.
Keywords: sedentary; occupational health; balance; active workstation